Employees’ intrapreneurial engagement initiatives and its influence on organisational survival - Falola, Hezekiah O.; Salau, Odunayo P.; Olokundun, Maxwell A.; Oyafunke-Omoniy, Comfort O.; Ibidunni, Ayodotun S.; Oludayo, Olumuyiwa A. (Business: Theory and Practice, 2018)
Employee intrapreneurial engagement is considered to be one of the fundamental initiatives that can help organisations to achieve a sustainable competitive advantage in the midst of economic hardship and stiff competition particularly in a volatile and competitive business environment. The main objective of this study is to examine how employees’ intrapreneurial engagement initiatives would influence organisational survival. Few studies analyse how employee intrapreneurial engagement may foster organisational survival. In order to bridge this gap, we conducted a survey with three main manufacturing companies in Nigeria. A descriptive research method (Structural Equation Model (AMOS 22)) was applied to analyse the two hundred and fifty-nine (259) copies of valid questionnaire completed by the respondents using stratified and simple random sampling techniques. However, the study indicated that fostering employees’ intrapreneurial engagement have positive significant implications on organisational survival. This suggests that employees’ empowerment, involvement, autonomy, relationships and reward system have significant effects on organisational survival. It is therefore recommended that organisations should challenge their employees by providing them with autonomy and the freedom to innovate and carve out spaces for them to take risks and experiment. The insights discovered from this study would help to facilitate stakeholders to develop or foster employee intrapreneurial engagement and strong institutional strategies to ensure organisational survival.